Ocular manifestations and surgical interventions in pediatric patients with Koolen-de-Vries syndrome. (4th March 2021) - Prat, Daphna; Katowitz, William R.; Strong, Alanna; Katowitz, James A.
ABSTRACT: Background : Koolen-de Vries syndrome (KdVS) (OMIM #610443) or 17q21.31 microdeletion syndrome, is a rare genetic disorder characterized by developmental and speech delay, intellectual disability, epilepsy, hypotonia, characteristic facial features, and congenital malformations of multiple organs. The purpose of the current study was to describe ocular manifestations and surgical interventions in six KdVS pediatric patients, and to review the ocular associations of this condition. Materials and Methods : A retrospective review of consecutive KdVS subjects who were treated in the ophthalmology department at The Children's Hospital of Philadelphia over a 12-year period (2009–2020) was performed. Main Outcome Measures were ocular and ocular adnexal abnormalities, and ophthalmic surgical interventions. Results : Six patients were included (4 females (67%), mean age of 3.1 years (range 0.1 to 8.1 years)). The most common ocular findings were strabismus (n = 3/6, 50%), ptosis (n = 3/6, 50%), and hyperopia (n = 3/6, 50%). Two patients had amblyopia. Four patients required surgical intervention, including strabismus repair (n = 3), and bilateral levator resection and medial canthopexies (n = 1). Conclusions : KdVS is associated with various ocular and ocular adnexal abnormalities. Most commonly ptosis, strabismus and hyperopia. Most cases required surgical intervention, most commonly strabismus repair. These findings mandate early ophthalmic evaluation with regular follow-up in this unique group of children.